THE EFFECT OF FINANCIAL LEVERAGE ON PROFITABILITY: AN EMPIRICAL ANALYSIS OF RECAPITALIZED BANKS IN GHANA - Bunyaminu, Alhassan; Yakubu, Ibrahim Nandom; Bashiru, Shani (International Journal of Accounting & Finance Review, 2021)
In this study, we examine the impact of financial leverage on profitability of recapitalized banks in Ghana over the period 2008-2017. Based on the random effects and fixed effects estimation strategies, our findings reveal that leverage exerts a significant negative effect on banks’ profits regardless of the proxy of profitability. This provides empirical support for the pecking order theory. The results also establish that bank size positively and significantly enhances profitability. In light of our findings, we conclude that financial leverage is detrimental to banks' profit growth in Ghana.JEL Classification Codes: G21, G30.